Intra-household Variation in Pathways to Care for Epilepsy and Mental Disorders in Eastern Uganda - Sarkar, Nandini D. P.; Bardaji, Azucena; Baingana, Florence K.; Rivera, Joan Muela; Criel, Bart; Bunders-Aelen, Joske; Grietens, Koen Peeters (Frontiers in Public Health, 2021)
Integrating mental, neurological, and substance use (MNS) health care into the public health system has become a global priority, with mental health and well-being now being part of the Sustainable Development Goals. In the aim to provide good quality care for MNS disorders, understanding patients’ pathways to care is key. This qualitative study explores the pathways to care of patients attending an outpatient mental health clinic of a district hospital in eastern rural Uganda, from the perspectives of their caregivers. 27 in-depth interviews were conducted with caregivers of MNS patients visiting the clinic, with a focus on four case-presentations. Data analysis consisted of thematic and emergent content analyses using NVivo 11. Results across all interviews highlight that chosen help-seeking itineraries were largely pluralistic, combining and alternating between traditional healing practices and biomedical care, regardless of the specific MNS disorder. Intra-household differences in care seeking pathways – e.g. where one patient received traditional help or no care at all, while the other received biomedical care – depended on caregivers’ perceived contextual illness narrative for each patient, in combination with a variety of other factors. If interpreted as a form of bewitchment, traditional medicine and healing was often the first form of care sought, while the mental health clinic was seen as a recourse to “free” care. Patients, especially younger children, who showed visible improvements once stabilized on psychotropic medication was a source of motivation for caregivers to continue with biomedical care at the mental health clinic. However, stock-outs of the free psychotropic medication at the clinic led to dissatisfaction with services due to out-of-pocket expenses and precipitated returning to alternative therapy choices. This article showcases the importance of understanding the complex and varied combinations of individual, cultural, socioeconomic and structural factors that may affect caregivers’ choices of pathways to care for patients with MNS disorders in eastern rural Uganda. These cumulative complex processes and context-specific help-seeking behaviors, which ultimately impact patient treatment and MNS health outcomes, need to be first acknowledged, understood and taken into account if we are to promote more inclusive, effective and integrated public mental health systems globally.